Efficient immunoglobulin gene disruption and targeted replacement in rabbit using zinc finger nucleases. - Tatiana Flisikowska (Public Library of Science (PLoS), 2011)
Rabbits are widely used in biomedical research, yet techniques for their precise genetic modification are lacking. We demonstrate that zinc finger nucleases (ZFNs) introduced into fertilized oocytes can inactivate a chosen gene by mutagenesis and also mediate precise homologous recombination with a DNA gene-targeting vector to achieve the first gene knockout and targeted sequence replacement in rabbits. Two ZFN pairs were designed that target the rabbit immunoglobulin M (IgM) locus within exons 1 and 2. ZFN mRNAs were microinjected into pronuclear stage fertilized oocytes. Founder animals carrying distinct mutated IgM alleles were identified and bred to produce offspring. Functional knockout of the immunoglobulin heavy chain locus was confirmed by serum IgM and IgG deficiency and lack of IgM(+) and IgG(+) B lymphocytes. We then tested whether ZFN expression would enable efficient targeted sequence replacement in rabbit oocytes. ZFN mRNA was co-injected with a linear DNA vector designed to replace exon 1 of the IgM locus with ∼1.9 kb of novel sequence. Double strand break induced targeted replacement occurred in up to 17% of embryos and in 18% of fetuses analyzed. Two major goals have been achieved. First, inactivation of the endogenous IgM locus, which is an essential step for the production of therapeutic human polyclonal antibodies in the rabbit. Second, establishing efficient targeted gene manipulation and homologous recombination in a refractory animal species. ZFN mediated genetic engineering in the rabbit and other mammals opens new avenues of experimentation in immunology and many other research fields.